2008
DOI: 10.1007/s12282-008-0082-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound screening of breast cancer

Abstract: Ultrasound (US) screening of breast cancer was surveyed with the results of breast screening combined with mammography (MMG), US and clinical breast examination (CBE) at Ibaraki Health Service Association. Breast cancer is common among women in their late 40s in Japan, who tend to have small and dense breasts. Our results showed that US works as well as MMG in detecting breast cancers in women in their 40s, and both modalities are compensatory. There are many reports that the combination of MMG and US is a sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 16 publications
1
28
0
2
Order By: Relevance
“…If a patient had more than one screening US examination with negative findings before the diagnosis, the examination closest to the diagnosis of cancer was used for the analysis. Forty-eight women with an interval of more than 24 months between the two US examinations and 46 women whose cancers were detected by means of (8)(9)(10). The use of supplemental screening US for women with dense breasts has also been further reinforced with the implementation of Connecticut Public Act 09-41, which now requires radiologists in that state to inform patients with dense breasts that they may gain additional benefit from US (11).…”
Section: Study Populationmentioning
confidence: 99%
“…If a patient had more than one screening US examination with negative findings before the diagnosis, the examination closest to the diagnosis of cancer was used for the analysis. Forty-eight women with an interval of more than 24 months between the two US examinations and 46 women whose cancers were detected by means of (8)(9)(10). The use of supplemental screening US for women with dense breasts has also been further reinforced with the implementation of Connecticut Public Act 09-41, which now requires radiologists in that state to inform patients with dense breasts that they may gain additional benefit from US (11).…”
Section: Study Populationmentioning
confidence: 99%
“…Six previous single-center studies 16 and three multicenter trials 79 have shown supplemental screening breast ultrasound significantly increases detection of node-negative invasive breast cancer in women with mammographically dense breast tissue on the first, prevalence screen, consistently increasing cancer detection (yield) by 3.5 per 1000 in single-center studies and 4.2 to 4.4 per 1000 in multicenter trials. The vast majority of cancers seen only on ultrasound have been node-negative invasive breast cancers.…”
Section: Introductionmentioning
confidence: 96%
“…It is important however to understand that a suspicious finding on mammography requires a more expensive and resource intensive technique such as a vacuum assisted stereotactic biopsy, whereas positive findings on ultrasound can be sampled by simpler faster and less expensive procedures and sometimes by means of fine needle aspiration [25]. The other drawback with the use of ultrasound is time to perform a whole breast ultrasound which has been reported to be between 10 and20 mins per bilateral examinations [24,[26][27][28]. It requires about 20 min performing a meticulous bilateral screening ultrasound; this drawback imposes a limitation of the number of screening studies that can be performed by a radiologist.…”
Section: Breast Mri and Breast Ultrasoundmentioning
confidence: 99%